Job characteristics as determinants of career change. (2017) - Jothi, S.; Wesley, J. Reeves
The IT industry has gained significance in India as it employs the largest number of the workforce every year. The advent of this industry has caused significant changes in the characteristics of work. Employees experience a higher level of job burnout, career plateau, work-family conflict, job insecurity and lower career satisfaction, resulting in turnover intentions. Extant literature suggests that the nature of work compels employees to accept subpart jobs, called as career change. A conceptual framework consisting of job burnout, career plateau, job insecurity, career satisfaction and work-family conflict as independent variables and career change as the dependent variable is developed. An adopted scale was used to collect data. The measurement model was tested using confirmatory factor analysis and the structural model using structural equation modelling. Results show job burnout, career satisfaction, and career plateau predicts career change. Implications of this study and recommendation for future studies were discussed.